2017
DOI: 10.1371/journal.pone.0178857
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of arsenic trioxide and lithium chloride augments viability reduction and apoptosis induction in human rhabdomyosarcoma cell lines

Abstract: Rhabdomyosarcomas (RMS) are the most prevalent soft tissue sarcomas affecting children and adolescents. Despite intensive treatment consisting of multimodal chemotherapy and surgery RMS patients diagnosed with metastatic disease expect long term survival rates of only 20%. Often multidrug resistance arises upon initial response emphasizing the need for new therapeutic drugs to improve treatment efficiency. Previously, we demonstrated the efficacy of the FDA approved drug arsenic trioxide (ATO) specifically inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
2
8
0
1
Order By: Relevance
“…6e). Further, we confirmed LiCl was working effectively by observing a significant increase in whole cell β-catenin levels via immunofluorescence (Supplementary Figure 4c, d) as previous studies have shown that LiCl-induced GSK3β phosphorylation results in β-catenin stabilisation[103][104][105][106] , .…”
supporting
confidence: 80%
“…6e). Further, we confirmed LiCl was working effectively by observing a significant increase in whole cell β-catenin levels via immunofluorescence (Supplementary Figure 4c, d) as previous studies have shown that LiCl-induced GSK3β phosphorylation results in β-catenin stabilisation[103][104][105][106] , .…”
supporting
confidence: 80%
“…Synergistic combination effects of ATO and fibroblast growth factor receptor inhibitor has been shown in squamous cell lung carcinoma 23. And combination with lithium chloride (LiCl) showed reduction in cell viability reduction colony formation, and cell death in rhabdomyosarcomas (RMS) 24. ATO plus PX-478 (hypoxia-inducible factor-1 inhibitor) achieves effective treatment in pancreatic ductal adenocarcinoma 25.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dual inhibition of GLI1/2 and Hh-related protein smoothened (SMO) or glycogen synthase kinase 3 (GSK3) led to a significant reduction in colony formation in both ARMS and ERMS cells. However, 3D-spheroid culture, as a better representation of the in vivo situation, showed limited additive effects of these combinations (52,53). The current in vitro and in vivo models do not allow for direct translation of these combinations to a clinical setting.…”
Section: Hedgehog Signalingmentioning
confidence: 99%